The Other Triad of Space: Doreen Massey and the Geometries of Power - Ávila Delgado, Noelia (Boletín de Estudios Geográficos, 2023)
Among the most relevant contributions of Doreen Massey are the reflections she made on space and that she developed in parallel with her proposal of the geometries of power, from which she conceives it as: 1) relational, 2) multiple, and 3) ) open. Based on documentary and interpretive research that recovers the author’s conceptual corpus, the aim of this paper is to show the implications of this theory, expose what each of these postulates implies, and reveal their potential for social theory. . It is concluded that Massey’s represents a long-range epistemological formulation that has currently become a fundamental reference to explain the different phenomena related to space, and some other fundamental contemporary processes, such as the Covid-19 pandemic, a fact that has been It is approached as a closing with the intention of showing the validity and dynamism of its approaches.